How to Promote Learning in African Countries? Open d-learning System Based on an Open Content - Daoudi, Najima; Amrous, Naila; Ettaki, Badia (International Journal of Emerging Technologies in Learning (iJET), 2013)
The learning process has always been a privileged appeal for individuals to improve their knowledge and skills to enable them to become more productive and contribute to the sustainable development of society. However, poverty in most African countries generally, hampers the implementation of the learning process-face. These prove to be expensive when considering the cost of construction of facilities, teaching materials and also paying the teachers for tracking learners and contents production. To overcome the various constraints (personal, social and pedagogic) that impede the classical process of learning, we propose to use an open d-learning system.It is a learning system that relies largely on contents 2.0 produced by researchers and experts and open content (open archives and open journal). Digital libraries can provide our system with a favorable environment in order to engage learners, motivate them and orientate them along their researches. Pedagogy and technology go together in this system to provide a quality learning environment. Indeed, management systems for the content of the company ECM provide an environment capable of managing the content despite their diversity and dispersal in several servers. The recommended pedagogy is the one which is active and constructive centered on the learner. An open d-learning plays an important role for the promotion of human development and thereby ensures the progress and changes in developing countries. The proposed system deals with an open generic and modular design to meet scalability of content and learning services always evolving. It allows access through several data -processing objects in the first level. The second one provides different learning services such as exercises, assessments, conducting practical work or projects. An intermediate level has been proposed to capitalize and gather the free content on the web identified as being useful for learning to enable their re-use and their sustainability. Finally, the fourth level which is in the form of an educational heritage consists of a free content but rich and varied. Such a system would be able to offer new opportunities for the countries in the process of development to guarantee human development and to become thus more competing at the era of globalization and the emergent technological development.